New Plants for Florida: Molecular Genetics for Enhanced Plant Breeding - Fredy Altpeter; Dave Clark; Fred Gmitter; Dennis Gray; Curt Hannah; Gloria Moore; Jane Polsten; Richard L. Jones; Mary Duryea; Berry J. Treat (EDIS)
In recent years, FAES breeders have joined forces with FAES molecular geneticists. Molecular genetics can make breeding programs more efficient, accelerate progress in breeding, and enable the introduction of novel traits.  This document is part of Circular 1440, a publication of the Florida Agricultural Experiment Station, the Agronomy Department and IFAS Communication Services, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Publication date August 2003. Originally published as a booklet by IFAS Communication Services June 2003.